ChemInform Abstract: Sodium Perchlorate Catalyzed Synthesis of 2, 4, 6‐Trioxotetrahydropyrimidin‐5(2H)‐ylidene Derivatives as Antioxidant Agents. Issue 6 (21st January 2016) - Gireesh, T. M.; Kamble, Ravindra R.; Dorababu, A.; Somagond, Shilpa M.
Abstract: The compounds (III) are easily formed from chalcones (I) appended to sydnone in the presence of sodium perchlorate as Lewis acid.